Antifungal Activity of Nontoxic Nanocomposite Based on Silver and Reduced Graphene Oxide against Dermatophytes and Candida spp - Gottardo, Bianca [UNESP]; Zoccal, Andreza R. M. [UNESP]; Maschio-Lima, Taiza [UNESP]; Lemes, Thiago H. [UNESP]; Paziani, Mario H.; Von Zeska Kress, Marcia R.; Perfecto, Tarcísio M. [UNESP]; Almeida, Margarete T. G.; Volanti, Diogo P. [UNESP] (My University, 2023)
Dermatomycoses are typical hair, skin, or nail infections caused mainly by dermatophytes and nondermatophytes: Trichophyton, Microsporum, Epidermophyton, and Candida. In addition to the esthetical impact, pain, and nail deformity, these mycoses can be a source of severe disease. The high cost of treatment, toxicity, and the emergence of resistant infectious agents justifies research into new drugs. This work evaluates the fungicidal activity of nanocomposites (NCs) based on reduced graphene oxide (rGO) loaded with silver (Ag) nanoparticles (rGO/Ag) against clinical isolates of dermatophytes and Candida species. This is an unprecedented study in which, for the first time, hybrid nanocompounds based on Ag/rGO were tested against Epidermophytom, Microsporum, and Trichophyton species (dermatophytes agents). In this paper, we synthesize rGO using different concentrations of Ag by hydrolysis of metal salt AgNO3 and follow the growth of nanocrystals on sheets of rGO provided by the NaBH4. The NCs were analyzed by X-ray diffraction analysis, and the NC morphology, silver distribution on the rGO surface, and crystalline information were investigated by transmission electron microscopy. Antifungal susceptibility assay was performed by the microdilution method based on modified Clinical and Laboratory Standards Institute (CLSI) protocol. Time-kill kinetics was conducted to monitor the effect of the composite to inhibit fungal cells or promote structural changes, avoiding germination. The toxicological evaluation of the NCs was born in an in vivo model based on Galleria mellonella (G. mellonella). Minimum inhibitory concentration (MIC) values of the rGO/Ag NCs ranged from 1.9 to 125 μg/mL. The best inhibitory activity was obtained for rGO/Ag12%, mainly against Candida spp. and Epidermophyton floccosum. In the presence of sorbitol, MIC values of rGO/Ag NCs were higher (ranging from 15.6 to 250 μg/mL), indicating the action mechanism on the cell wall. Both yeast and dermatophytes clinical isolates were inhibited at a minimum of 6 and 24 h, respectively, but after 2 and 12 h, they had initial antifungal interference. All hybrid formulations of rGO/Ag NCs were not toxic for G. mellonella. This study provides insights into an alternative therapeutic strategy for controlling dermatomycoses.
Keywords: antifungals; antimicrobial agents; in vivo tests; metal nanoparticles